(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to provide training and practical guidance to the community of Buku Utara Village, Belang District, Southeast Minahasa Regency, on the processing of Kappaphycus alvarezii into carrageenan. The program was designed to address the limited knowledge and skills of local seaweed farmers in processing seaweed beyond dried raw materials. The activities consisted of preliminary observation, coordination with village authorities and community partners, counseling, practical training, mentoring, and evaluation. The training was conducted on November 8, 2025, and involved 20 participants consisting of K. alvarezii farmers and members of the coastal community. Participants were introduced to the potential uses of carrageenan and directly practiced the processing stages demonstrated by the training team. Evaluation was conducted through discussion, questions and answers, and observation of participant involvement during the training. The activity indicated that participants gained an understanding of the potential of K. alvarezii as a raw material for carrageenan production and were able to participate directly in the demonstrated processing activities. The program provided an initial foundation for developing household-scale seaweed processing and value-added products in Buku Utara Village.